IMPLEMENTASI PENDIDIKAN KARAKTER DALAM KEGIATAN EKSTRAKURIKULER DI SMA NEGERI 1 PEMALANG - Fajridyah Handayani; muhdi muhdi; Ghufron Abdullah (Jurnal Manajemen Pendidikan (JMP), 2016)
The focus in this thesis research is: (1) How is the policy of character education in extracurricular activities in SMAN 1 Pemalang?; (2) How character values in extracurricular activities implemented in SMAN 1 Pemalang? The purposes of this thesis were (1) To recognize the character of education policies in extracurricular activities in SMAN 1 Pemalang and (2) to recognize the implementation of character values in extracurricular activities in SMAN 1 Pemalang.This thesis collects data using interviews, observation and documentation. Data is analyzed using interactive models with the following manner: (1) data collection, (2) data reduction, (3) presentation of data, and (4) conclusion.Based on the results of research and discussion of the results obtained: (1) The Policy of character education in extracurricular activities in SMAN 1 Pemalang is contained in Document 1 Curriculum of SMA Negeri 1 Pemalang and Extracurricular Activities guide in SMA Negeri 1 Pemalang; (2) The implementation of character education in extracurricular activities are divided into 4 groups, namely psychosocial though the heart, though the thought, though sports and liver. Extracurricular activities of religious yet to be seen, only religious activities habituation in terms of worship through Islamic spirituality, christian spirituality and Catholic spirituality; (3) The program of activities of habituation should also be made more orderly for the implementation of the implementation of character education in extracurricular activities can be monitored more success; (4) extra in terms of character education has not been fully implemented, only the discipline that becomes a reference to it in future assessments in character education should also be done in any extracurricular activities.